Adherence to moderate to high-intensity exercise in patients with fibromyalgia: A narrative review of the physiological and psychological factors involved (Research, Society and Development, 2024)
The present study aims to investigate the effects of functional training on balance and the proprioceptive system in individuals with visual impairment. It is essential to highlight that people with visual impairment face specific difficulties and several challenges, especially with regard to quality of life, given that their visual perception of the environment is greatly reduced. This limitation compromises the ability to perform daily activities autonomously, directly impacting their quality of life. In this context, functional training emerges as a promising alternative to improve balance and the proprioceptive system in individuals with visual impairment, thus promoting a better quality of life. To achieve the proposed objectives, a narrative literature review was carried out, based on theoretical studies related to the theme addressed. The research used recognized databases, such as LILACS, BVS, CAPES and SciELO, to compose the theoretical and methodological framework of the study. The study concluded that functional training promotes improvements in balance, proprioception and motor coordination in people with visual impairment, contributing to their autonomy and fall prevention.